The effectiveness of dynamic tape on young male handball athletes` single leg hop test and dynamic balance: a randomized controlled trial - Pinto da Costa, C.; Guimarães, B.; Cardoso, R.; Moreno, B.; Carvalho, A. C.; Joana, M.; Barreto, J.; Aguiar Branco, C. (15th YES Meeting, 2020)
Dynamic Tape has a positive effect in the one-leg horizontal jump and in the dynamic balance when applied in the lower limb of young handball athletes. Therefore, its application as anauxiliary measure to the practice of this sport, might contribute to better sports performance and results.